Optimalisasi Pemanfaatan Air Sungai untuk Pemenuhan Kebutuhan Irigasi - Liany Hendratta; Dave Steve Kandey (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2021)
Polimaan weir that utilizes water of the Polimaan River, is used to irrigate rice fields covering an area of 297.96 Ha. As a result of decrease in the discharge of Polimaan River, there was water shortage within the service area of Polimaan weir. In one planting season, half the total service area did not get sufficient water supply. so there is urgency to evaluate water availability of Polimaan river to keep up the performance of the irrigated padi-field. This study aimed at assessing the water availability of the Polimaan River at the point of the weir and calculating the water balance in order to optimally meet irrigation water needs. Analysis of water availability and demand were carried out using secondary data and direct observation at the study site. Water availability was evaluated using the NRECA model. The closest calibration result was with the accuracy level calculated using the Nash-Sutcliffe Coefficient (E) of 0.731. Water requirements were examined by simulating the cropping system ie.: varying the cropping pattern and changing the rotation coefficient of tertiary plots. After 18 variations of cropping pattern only 3 patterns did not show that the patterns experienced water shortages. They included: 2 cropping patterns which used a water distribution system for 3 groups and 1 other pattern which implemented it for 2 groups. The three cropping patterns were carried out only 1 planting season for each group with different scheduling and rotation was carried out for each tertiary plot. Consequently, only half the irrigated land can be utilized in each planting season.